11 Reporting lab results: the cause of, and the solution to, the overdiagnosis problem. (20th August 2018) - McCormack, James; Doust, Jenny; Bell, Catherine
Abstract : Aims/background: Lab test results likely drive two-thirds to three-fourths of medical decisions. Unfortunately lab test reports rarely mention, or put into context, the analytic and biologic variation inherent with every result. This leads us in healthcare to, likely somewhat knowingly, sell preeminent precision even though we all know in our heart of hearts we can only deliver educated estimates. Objectives: In this seminar we will: outline the problem of lab test measurement and reporting and how it contributes to the overdiagnosis problem hopefully offer some useful tips and suggestions for how to deal with this extremely important and relevant healthcare conundrum. Methods: This seminar will introduce, via a series of brief presentations, the problem of lab value variation using examples of glucose, cholesterol, blood pressure, bone density and Vitamin D among others. We will then use interactive case studies to allow participants to learn and practice how to incorporate this issue into better shared-decision making with patients. Conclusions: The problem with lab test variation is that it is not a fixable problem, it is only a knowable problem. Hopefully by the end of this session, participants will be armed with enough information to help them maneuver around this issue in an informed and practical manner.